2012
DOI: 10.1111/j.1651-2227.2012.02658.x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes, coeliac disease, multiple sclerosis and chronic arthritis in first‐degree relatives of patients with juvenile idiopathic arthritis

Abstract: Autoimmune diseases cluster in families with a child with JIA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
(42 reference statements)
2
8
1
1
Order By: Relevance
“…In our cohort, overall prevalence of autoimmune disorders in relatives was significantly increased, consistent with data from previous studies 6 24 25. But in contrast to those studies, which found the highest prevalence in the oligoarticular group, we found the highest prevalence in the psoriatic arthritis group, followed by the enthesitis-associated group and then by the oligoarticular group, as a result of a different composition of the study populations.…”
Section: Discussionsupporting
confidence: 88%
“…In our cohort, overall prevalence of autoimmune disorders in relatives was significantly increased, consistent with data from previous studies 6 24 25. But in contrast to those studies, which found the highest prevalence in the oligoarticular group, we found the highest prevalence in the psoriatic arthritis group, followed by the enthesitis-associated group and then by the oligoarticular group, as a result of a different composition of the study populations.…”
Section: Discussionsupporting
confidence: 88%
“…Prahalad et al [18] underlined how AITD were the most frequent associated diseases while Huang et al [19] revealed also the presence of psoriasis, ankylosing spondylitis and SLE. Pohjankoski et al [20] studied the presence of IDDM, CD, MS and chronic arthritis in 355 families of JIA patients showing an overall prevalence of 21.4%. The data of a large cohort of patients in the United States have recently been published [21] showing that the prevalence of autoimmunity is increased among the relatives of JIA subjects compared to those of JDM with a greater proportion of inflammatory arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…It has become increasingly clear that autoimmune diseases cluster in individuals and families 14 15. In line with this, genetic variations have been identified that are associated with more than one autoimmune disease, like rheumatoid arthritis (RA), type 1 diabetes mellitus, autoimmune thyroid disease, inflammatory bowel disease, systemic lupus erythematosus, multiple sclerosis, and also JIA 1620.…”
Section: Introductionmentioning
confidence: 95%